The College Academic Self-Efficacy Scale (CASES); An Indonesian Validation to Measure the Self-Efficacy of Students - Ifdil, Ifdil; Bariyyah, Khairul; Dewi, Ari Khusuma; Rangka, Itsar Bolo (Jurnal Kajian Bimbingan dan Konseling, 2019)
This study examines the inventory properties of the Indonesian version of The College Academic Self-Efficacy Scale (CASES) which is originally Western, and was developed by Owen, S. V., & Froman, R. D. in 1988 to determine the level of student self-efficacy. The multi-stage random sampling method was used with 342 students as participants in Indonesia. Furthermore, the validity was analyzed using Cronbach’s alpha item analysis that shows the coefficient of α > .3, and the data showed that 33 items of Indonesian CASES were valid. In addition, as regards reliability, Cronbach’s alpha was also used for the analysis, and the result shows that reliability coefficient of the Indonesian version of CASES was .931. Furthermore, it was concluded that the validity of CASES was satisfying to measure students’ self-efficacy, and the construct of Indonesian CASES can be helpful and applicable in understanding student self-efficacy and ready to be used in subsequent researches.